2017
DOI: 10.3748/wjg.v23.i47.8387
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cigarette smoking on recurrence of hyperlipidemic acute pancreatitis

Abstract: AIMTo investigate the impact of cigarette smoking on the recurrence rate and recurrence-free survival in patients with hyperlipidemic acute pancreatitis (HLAP).METHODSA total of 863 patients were admitted to our hospital for acute pancreatitis (AP) from January 2013 to March 2016, of whom 88 diagnosed with HLAP were enrolled in this retrospective study. Demographic data, medical history, previous episodes of pancreatitis, consumption of alcohol and cigarettes, as well as biochemical and hematological data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
1
19
1
2
Order By: Relevance
“… 27 The diagnosis of HTGP was confirmed if patients had AP with serum total triglyceride (TG) >11.3 mmol/L (1000 mg/dL), or a serum TG level of 5.65–11.3 mmol/L accompanied by chylous serum and the absence of other risk factors for AP. 5 The exclusion criteria were (1) indication of biliary, alcoholic, autoimmune, drug-induced or pancreatic tumor-related etiology of AP; (2) poor CT imaging of the abdomen; (3) pregnancy. This study was performed with approval from the ethics committee of the First Affiliated Hospital of Wenzhou Medical University (KY2019–011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 The diagnosis of HTGP was confirmed if patients had AP with serum total triglyceride (TG) >11.3 mmol/L (1000 mg/dL), or a serum TG level of 5.65–11.3 mmol/L accompanied by chylous serum and the absence of other risk factors for AP. 5 The exclusion criteria were (1) indication of biliary, alcoholic, autoimmune, drug-induced or pancreatic tumor-related etiology of AP; (2) poor CT imaging of the abdomen; (3) pregnancy. This study was performed with approval from the ethics committee of the First Affiliated Hospital of Wenzhou Medical University (KY2019–011).…”
Section: Methodsmentioning
confidence: 99%
“… 2 Notably, hypertriglyceridemic pancreatitis (HTGP), which accounts for up to 10% of AP cases, occurs in the presence of hypertriglyceridemia with no signs of other causes. 5 Recent reports have indicated that the incidence of HTGP in Asia is increasing, 3 , 6 and is higher than that reported in Western countries, 7 which and ranked as the third leading cause for AP. 8 …”
Section: Introductionmentioning
confidence: 97%
“…Patients with SAP had a significantly higher NIHSS score on admission (9.0 vs 2.0), and higher fibrinogen (4.4 g/L vs 3.6 g/L), leukocyte counts (9.7×10 9 /L vs 7.3×10 9 /L). We selected 10.0×10 9 /L as the leukocyte cutoff point based on previous studies 21,22. The best cutoff value for fibrinogen in the training cohort, as revealed by ROC analysis, was 3.68 g/L.…”
Section: Resultsmentioning
confidence: 99%
“…A recent comprehensive study analyzing 2810 patients demonstrated that cigarette smoking and drinking were associated with non-gallstone-related pancreatitis, including hypertriglyceridemia-induced acute pancreatitis [18]. Another study noted that cigarette smoking might contribute to hyperlipidemic acute pancreatitis recurrence [19]. Future studies are needed to clarify possible changes in the metabolic and molecular characteristics of HIAP related to tobacco use and drinking.…”
Section: Discussionmentioning
confidence: 99%